THE DEMAND OF POLITICAL RIGHTS: CASE STUDY SPECIAL AUTONOMY REGION STATUS FOR MALAY MUSLIM PATANI IN SOUTHERN THAILAND - Naeem Hayipiyawong (MIHI UMY, 2015)
This thesis discuss about the demand of political rights: case study special autonomy region status for Malay Muslim Patani in southern Thailand, there are Pattani, Yala, and Narathiwat. Malay Muslim Patani feelings about the unfair treatment of administration from central government. Therefore Malay Muslim Patani demand the right of self-determination as proposal of political solution in concepts of autonomy and recognition of their language, culture, religion, control of administrative system and their resources in Southern Thailand. By a change of administrative systems from centralization to autonomy status to determine decentralization administrative system to local government with elected governors and deputy governors by local people. The practical central government should present an act to promote the autonomy status to the provincial areas as the following give distribute the authority of responsibility into local provinces as what they needs and give decentralize the authority of decision-making in local needs. The thesis tries to analyze two theories are employed to analyze the demand of political rights: case study Special Autonomy Status for the ethnic minority group Malay Muslim Patani in Southern Thailand (Patani), (1). Right of self-determination, (2). Autonomy Region. In this research, extensive of relevant published materials such as books, journals, reports, newsletters, official website and other are used sources a wide variety of references in related topics to conduct the analysis.